Sistema hibrído com eletro-fenton e adsorção para tratamento de águas residuárias de tingimento de pedras semipreciosas - Ludwig, Bianca Carolina (2018)
The processing of semi-precious stones, mainly in the dyeing stage, requires large volumes of water, which generate effluents with high concentrations of dyes, which are harmful to aquatic and human life, if not treated properly. These contaminants have low degradability and therefore need advanced treatmentmethods. Thus, the objective of this study is to develop a hybrid treatment system based on electro-Fenton and fixed bed column adsorption applied to the actual effluents containing synthetic organic Rhodamine B dye. For this, the effluent was collected in a stone processing industry and was characterized in terms of absorbance, color, pH, chemical oxygen demand (COD) and turbidity. Afterwards, electro-Fenton assays were performed, varying the current density (J), initial pH and concentration of Fenton reagent, in response to dye removal and energy consumption. The optimized condition was found at pH 2, current intensity of 110 A.m-2, initial concentrations of iron (II) of 1.25 g.L-1 and hydrogen peroxide of 0.033 mol.L-1. The adsorption isotherms of this resin show high affinity with the adsorbent, reaching adsorption capacity of 257.9 mg.g -1, according to the model of Langmuir. The rupture curves showed that the flow rate of 5 mL.min-1 is more adequate for the adsorption of Rhodamine B, and the Thomas model is able to predict the data of the rupture curves. In a hybrid system, the electro-Fenton system followedby adsorption was able to remove 99% of Rhodamine B, being an effective system for the treatment of effluents from the stone dyeing process, containing Rhodamine B.